Mechanisms for Host Immune Evasion Mediated by Plasmodium falciparum-Infected Erythrocyte Surface Antigens - Sakoguchi, Akihito; Arase, Hisashi (Frontiers in Immunology, 2022)
Plasmodium falciparum infection causes the most severe form of malaria. It has been hypothesized that P. falciparum directly suppresses host immune responses because sufficient acquired immunity is often not induced even by repeated P. falciparum infections in malaria-endemic areas. It is known that many kinds of P. falciparum-derived proteins are expressed on the surface of P. falciparum-infected erythrocytes (IEs), and these proteins have long been thought to be a key to the elucidation of the host immune evasion mechanisms. Our recent studies have revealed that the P. falciparum-derived erythrocyte surface antigen, RIFIN, the largest multiple gene family protein in the P. falciparum genome, suppresses host immune cell activation through direct interaction with human inhibitory immune receptors. In this review, we will discuss the molecular mechanisms for host immune evasion by P. falciparum-infected erythrocyte surface antigens. In addition, we will discuss the recently identified host immune response to P. falciparum using specialized antibodies that target host-P. falciparum-derived molecule interactions.